2020
DOI: 10.1088/2632-2153/ab7e1a
|View full text |Cite
|
Sign up to set email alerts
|

Methods for comparing uncertainty quantifications for material property predictions

Abstract: Data science and informatics tools have been proliferating recently within the computational materials science and catalysis fields. This proliferation has spurned the creation of various frameworks for automated materials screening, discovery, and design. Underpinning these frameworks are surrogate models with uncertainty estimates on their predictions. These uncertainty estimates are instrumental for determining which materials to screen next, but the computational catalysis field does not yet have a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 32 publications
3
170
0
Order By: Relevance
“…A more general study (including GPR as well as other types of ML methods) of uncertainty quantification with relevance to physical sciences was reported in ref ( 201 ). This study also includes a didactic overview of uncertainty quantification methods.…”
Section: Validation and Accuracymentioning
confidence: 99%
“…A more general study (including GPR as well as other types of ML methods) of uncertainty quantification with relevance to physical sciences was reported in ref ( 201 ). This study also includes a didactic overview of uncertainty quantification methods.…”
Section: Validation and Accuracymentioning
confidence: 99%
“…In some instances, prediction errors due to model inadequacy can be handled by statistical correction of predictions, which may provide a reliable uncertainty measure [20]. Various surrogate methods have been developed for the estimation of prediction uncertainty, such as bootstrap-based methods, Gaussian process regression, neural networks and deep learning ensembles [21][22][23]. Gaussian process regression has been employed to identify particular calculations within a given dataset for which the uncertainties exceed a given threshold [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…[135] Recently Tran et al comprehensively reviewed the various uncertainty quantification methods discussed above, and found that using the convolutional neural network feature in the Gaussian process provides the best uncertainty estimates. [136] Neural Network: Neural network models are typically the most flexible and the most accurate models. [101,103,104,[137][138][139][140] A neural network model can be thought of as a customized sequence of mathematical operations.…”
Section: Machine Learning Methodsmentioning
confidence: 99%